The Adverbial Hal Construction In The Thirtieth Juzʾ Of The Qur’an: A Syntactic And Semantic Analytical Study - Ali Asrun Lubis; Yunaldi Yunaldi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2026)
Purpose – This study aims to investigate the concept of al-ḥāl in the thirtieth Juzʾ of the Qur’an, focusing on its forms, classifications, and semantic functions. It seeks to provide a rigorous and detailed analysis of al-ḥāl within a specific Qur’anic corpus by examining its syntactic structures and contextual-semantic roles. Unlike previous studies that primarily offer broad theoretical categorizations, this research presents an applied linguistic analysis to address a significant gap in Qur’anic Arabic studies. Design/methods/approach – This study adopts a qualitative descriptive approach employing content analysis. The research corpus consists of verses from the thirtieth Juzʾ of the Qur’an selected purposively based on the frequency and contextual complexity of al-ḥāl constructions. Data analysis was conducted through three stages: (1) extraction of verses containing al-ḥāl; (2) typological classification into ḥāl mufrad (single-word circumstantial accusative), ḥāl jumlah (sentential circumstantial accusative), and ḥāl shibh al-jumlah (quasi-sentential circumstantial accusative); and (3) contextual-semantic interpretation supported by classical Qur’anic exegeses to determine their specific linguistic functions. Findings – The findings indicate that ḥāl mufrad is the most frequently occurring form due to its concise structure and precise semantic expression. Meanwhile, ḥāl jumlah appears predominantly in contexts requiring dynamic descriptions or psychological states, whereas ḥāl shibh al-jumlah functions as a complementary structure that provides situational and circumstantial background information. Furthermore, the distribution and variation of al-ḥāl are closely associated with the thematic and contextual framework of the verses, particularly those depicting eschatological scenes of the Day of Judgment. These findings corroborate previous studies while offering a more nuanced understanding through the integration of syntactic and semantic analyses within a specific Qur’anic corpus. Research implications – The study demonstrates the significance of contextualized analyses of al-ḥāl in understanding the linguistic and rhetorical dimensions of Qur’anic discourse. It contributes to the fields of Arabic linguistics and Qur’anic studies by providing an applied model for examining grammatical structures within their textual contexts. Moreover, the findings offer pedagogical implications for the teaching of Arabic grammar, emphasizing the importance of contextual and discourse-based approaches to the study of hal.